Analisis Wilayah Potensial dan Limitasi Berbasis Kawasan Rawan Bencana di Kecamatan Pangkalan Kuras, Kabupaten Pelalawan - Eggy Giofandi; dhanu Sekarjati; Yudhistira Prasetya; Arga Susilo; Andre Rahman; Teguh Kurnia; Ahyuni Ahyuni; Cipta Sekarrini (Universitas Medan Area, 2023)
Pangkalan Kuras District is a small part of Pelalawan Regency which is located in Riau Province. The resulting hydrometeorological disasters have impacts ranging from material losses and non-material losses such as loss of livelihoods, loss of life, damage to land, threatened habitat, and disruption of interaction with human activities. The purpose of this study is to provide the appearance of disaster-prone areas with the ultimate goal of producing potential disaster-safe areas through a spatial approach. This study uses data on topography, climatology, lithology, groundwater basins, soil characteristics, and land use. While the method applied is divided into 5 analyzes, namely analysis of area functions, land capability, land suitability, prone to flooding, and prone to landslides. The results of this study explain the division into 2 final areas, such as the potential area reaching 160,985 ha and the limiting area reaching 43,889 ha. This condition can be developed in various sectors to support the improvement of the community's economy by minimizing losses from various hydrometeorological disasters.